Analisis Efisiensi Teknis dan Efisiensi Ekonomis Usahatani Kentang di Kecamatan Sukapura Kabupaten Probolinggo - Isnaini, Anni Alifatul; Sudarko, Sudarko; Rokhani, Rokhani; Saifuddin, Saifuddin (Universitas Galuh, 2025)
This research aims to determine and analyze the level of technical efficiency and eco-efficiency in potato harvesting in the district of Sukapura Probolinggo. Usahatani potatoes have a vital role in the economy of the community in Sukapura district, Probolinggo district. The study aims to analyze the technical efficiency and economic efficiency of potato farming in the region. The analysis method involves collecting primary data from potato farmers through field surveys and in-depth interviews. The data collected included production costs, input used, harvest yields, and other factors affecting business efficiency. Technical efficiency analysis is carried out using the stochastic frontier approach, taking into account variability in data and identifying the level of technical efficiency of each farmer. Meanwhile, economic efficiency analysis involves comparisons between income and the total cost of production, providing a holistic picture of the economic well-being of potato farmers. The results of this research are expected to reveal key factors that affect the technical and economic efficiency of potato farming in Sukapura district. Policy recommendations that could increase productivity, reduce costs, and improve economic efficiency were proposed based on the findings of the analysis